Ecuador. La gestione dell’emergenza sanitaria in un contesto di estrema diseguaglianza: Il mondo e la lotta alla pandemia da COVID-19 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The impact of the current COVID-19 pandemic has brought up one of the major and outstanding problems afflicting Ecuador and Latin America in general, namely the drastic social and economic inequalities. The protection of the weekest and most vulnerable members of society - that is to say the most affected by the consequences of this pandemic crisis - would require cooperation among all State’s institutions. However, the dominance of the Head of State - with respect to other conter-powers of the Government - has been a ramarkable limit for a peaceful and fair collaboration between the executive and legislative branches in managing the emergency. In particular, it withheld the adoption of economic and social measures to support the most deprived sections of the population.
Keywords: Ecuador; COVID-19; inequalities; State of emergency; Moreno